Influence of seasonality on cetacean diversity, abundance, distribution and habitat use in the western Mediterranean Sea: Implications for conservation. Issue 5 (12th April 2017) - Arcangeli, Antonella; Campana, Ilaria; Bologna, Marco A.
Abstract: Cetaceans are key biological indicators of the status of marine waters and are protected under an extensive legislative framework. Research about these highly dynamic species is challenging, so seasonal cycles and patterns of distribution, especially in high sea areas, are still poorly understood. This study contributes to improving knowledge about cetacean occurrence in largely unexplored areas of medium‐latitudes in the western Mediterranean Sea. Systematic surveys were conducted along a trans‐regional transect over 3 years (October 2012 to September 2015) allowing consistent data collection over almost 60 000 km of effort through all seasons. Seasonal cetacean diversity was investigated using a 25 km 2 grid cell as a statistical unit to explore patterns of abundance, distribution, and habitat use in three marine sectors (Sardinian–Balearic, Bonifacio Strait, Tyrrhenian). All cetacean species regularly present in the Mediterranean basin were detected, with highest occurrence in fin whale and striped dolphin, followed by bottlenose dolphin and sperm whale. The Sardinian–Balearic sector generally showed higher species richness and diversity than the Tyrrhenian, where seasonal variations were more pronounced. The study suggested seasonal movements, especially for fin whale and striped dolphin, in the Sardinian–Balearic sector with peaks of occurrence during spring/summer and lower numbers during winter/autumn, and also delivered interesting insights to rarer pelagic species. The study identified areas/seasons in which the combined effect of high species diversity, abundance, significance of hot spots and presence of juveniles require increasing conservation effort. Results underline the important contribution of continuous monitoring in high sea areas to the implementation of adaptive protection measures.